Are we working (too) comfortably?: the systematic development of an intervention to support workers to move more while working at home - Divya Sivaramakrishnan; Claire Fitzsimons; Sarah Morton; Jillian Manner; Ruth Jepson; Ailsa Niven (International Journal of Behavioral Nutrition and Physical Activity, 2025)
Abstract Background Covid-19 accelerated a transformational change in working practices, with a considerable proportion of desk-based workers now engaged in home or hybrid working. Working at home appears to exacerbate the already elevated levels of unhealthy occupational sedentary behaviour, and there is a need to support employees to reduce sedentary behaviour while working at home. The aim of this study was to develop an intervention to support employees to reduce sedentary behaviour when working at home utilising the novel integration of the Six Steps in Quality Intervention Development (6SQuID) and Behaviour Change Wheel (BCW) intervention development frameworks. Methods We report on 6SQuID steps 1–5, with the Capability, Opportunity and Motivation influence on Behaviour (COM-B) model integrated into steps 1–4, providing a theoretical organising framework. In step 4, the intervention functions and behaviour change technique elements of the BCW were used to accurately and consistently specify the active ingredients of the intervention. The test and refine phase of 6SQuID (step 5) evaluated the acceptability of elements of the intervention with a sample of Scottish Government employees. Results The causal factors for employee sedentary behaviour while working at home were delineated, and theory of change/action models were constructed. Intervention components were developed to address causal factors and presented as a toolkit on an online platform. These comprised: 1) education on sedentary behaviour, 2) resources to aid intention formation and action planning, 3) strategies to increase movement, and 4) suggestions for support from colleagues/friends/family. Strategies aimed at line managers and organisations to support employees and create an organisational culture that enables employees to move more were also developed. The acceptability testing demonstrated the value of the toolkit format incorporating a suite of strategies, and feedback informed refinement of the toolkit. Conclusions This study addresses the urgent need to support employees to reduce sedentary behaviour while working at home. Using the novel application of integrated intervention development frameworks, a comprehensive intervention toolkit has been formulated and preliminarily tested. The toolkit comprises strategies and resources for employees, line managers and organisations. Further feasibility and effectiveness testing with a larger sample is recommended prior to large-scale implementation.